Regulatory Issues And Challenges On A2P SMS Communication In Malaysia - Asma Md. Isa; Wan Amizah Wan Mahmud; Arina Anis Azlan; Anita Morah Abas; Wan Idros Wan Sulaiman; Muhammad Adnan Pitchan; Umi Hamidaton Mohd Soffian Lee; Radin Anis Adlina Radin Hasbani (Science & Engineering Research Support Society, 2024)
Indexed by ERA